Knockdown of CUG‐binding protein 1 induces apoptosis of human laryngeal cancer cells. (19th August 2014) - Zhou, Yi; Ma, Hongzhi; Fang, Jugao; Lian, Meng; Feng, Ling; Wang, Ru
Abstract To investigate the role of CUG‐binding protein 1 (CUGBP1) in human laryngeal cancer, we employed lentivirus‐mediated short hairpin RNA (shRNA) to knockdown CUGBP1 expression in Hep‐2 cells. Depletion of CUGBP1 remarkably inhibited the proliferation of Hep‐2 cells. CUGBP1 knockdown induced cell cycle arrest in S phase, especially in the sub‐G1 phase, representing apoptotic cells. Knockdown of CUGBP1 in Hep‐2 cells markedly increased the expression of LIP and cleavage of PARP, which could contribute to apoptosis. Thus CUGBP1 has a critical role in modulating cell growth and apoptosis, and serves as a potential therapeutic target in laryngeal cancer.